Palengke village General Santos City mixed-use market and residential development - Yap, Justine Jules C.
In the field of commerce, central to its evolution is the creation of public markets where people convene not only to trade, but also to connect urban and rural economies, and to hold people of various cultures altogether. Aside from increasing access to affordable and fresh produce, markets serve as one of the community's original and traditional civic centers. However, through the changing times, the role of markets in the society took a step back to pave the way for supermarkets that are currently leading the roster. And while more people patronize their go to supermarkets, local public markets are still very much thriving, although experiencing more turbulence now more than ever, reason for the researcher to conduct a study on the redevelopment of the General Santos City Central Public Market. From the study, it was observed that the General Santos City Central Public Market is in a state of disrepair, with inefficient sanitation therein and little to no lighting caused by the defective roof, thus affecting the market vendors and consumers altogether. Truth be told, this has tainted the purchasing public's perception about the area. It has created a social divide among the consumers of the market. As such, the researcher addressed these drawbacks through its redevelopment and modernization to drive along with the city's continued progress towards urbanization. Significantly, the study yielded the conception that the integration of the redevelopment General Santos City central public market and the housing project aid in re-establishing the public market's character as the foundation of Philippine trade and commerce, revitalizing confluence among cultures, abetting the livelihood of local farmers, and promoting the general welfare and convenience of the informal sellers who live across the site. Culturally, it has a wide impact on community building. More so, the integration of both spaces facilities the promotion of every Filipino citizen's right to a dignified life. On a more substantive and view, this study underscores the value of architecture in appreciating and tracing one's roots.